If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -6y + 9(5y + 7) = 7 + -5(1 + -1y) Reorder the terms: -6y + 9(7 + 5y) = 7 + -5(1 + -1y) -6y + (7 * 9 + 5y * 9) = 7 + -5(1 + -1y) -6y + (63 + 45y) = 7 + -5(1 + -1y) Reorder the terms: 63 + -6y + 45y = 7 + -5(1 + -1y) Combine like terms: -6y + 45y = 39y 63 + 39y = 7 + -5(1 + -1y) 63 + 39y = 7 + (1 * -5 + -1y * -5) 63 + 39y = 7 + (-5 + 5y) Combine like terms: 7 + -5 = 2 63 + 39y = 2 + 5y Solving 63 + 39y = 2 + 5y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-5y' to each side of the equation. 63 + 39y + -5y = 2 + 5y + -5y Combine like terms: 39y + -5y = 34y 63 + 34y = 2 + 5y + -5y Combine like terms: 5y + -5y = 0 63 + 34y = 2 + 0 63 + 34y = 2 Add '-63' to each side of the equation. 63 + -63 + 34y = 2 + -63 Combine like terms: 63 + -63 = 0 0 + 34y = 2 + -63 34y = 2 + -63 Combine like terms: 2 + -63 = -61 34y = -61 Divide each side by '34'. y = -1.794117647 Simplifying y = -1.794117647
| 8x-1(6x+6)=8 | | 4x-30=-2x-6 | | x+2+4=4+4 | | 3z-3=2z+2 | | 7x-3(4x+8)=6x+12-9x | | 4x+22=7x+25 | | 3x^2+5x=-3 | | 6x+7x-57=38-6x | | 5(x-2)+11=6x-10 | | 31500-350x+90x-X^2=0 | | x^2+2x-11=-4x-4 | | (3y-2x+4)dx-(4x-3y-2)dy=0 | | 5(4h-7)=-18+6h | | 150=-0.8a+176 | | x^2+x+29=-9x+5 | | 16=-29k | | 2.5-0.03x=-1.19 | | .11x+29.99=35 | | 6.2x-5+x-2.1= | | -3(2b+4)+(7b-4)=0 | | 20m-12(m-3)=4 | | -29.99+0.11x=35 | | x^2-2-15=9 | | 2x-6+4x=42 | | -94=-8(2-r)+5r | | 7x^2+7x+10=0 | | -4=4+4v | | 8x+5+5x+3= | | 3(1.3)x-1=1.3 | | -94=-8(2-r)+5 | | 5a+4b+5a-2b= | | ax+5=bx+c |